Opera u svetlu antropološkog istraživanja - Dragana Antonijević (University of Belgrade, 2016)
Povodom knjige Vlado Kotnik. Opera, Power and Ideology. Anthropological Study of a National Art in Slovenia. 2010. Peter Lang, Internationaler Verlag der Wissenschaften